2008
DOI: 10.1038/sj.ki.5002603
|View full text |Cite
|
Sign up to set email alerts
|

Complementary use of peritoneal and hemodialysis: Therapeutic synergies in the treatment of end-stage renal failure patients

Abstract: The simultaneous use of peritoneal dialysis (PD) and hemodialysis therapy has been studied both in established PD patients who are experiencing problems with their dialysis treatment that might otherwise prompt a change in modality, and in patients new to dialysis. The application of combination therapy allows in incident patients a partial separation of solute clearance and ultrafiltration, optimizing each modality within that overall delivery. This article discusses the published experience of combination tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Previously, we reported that the mean age of patients who selected "PD first" were younger compared with that of patients on HD [16]. In the present study, there were no differences in mean age of patients who needed HD as complementary dialysis modality and those patients who started PD as "PD first", indicating that a larger portion of PD patients needed HD as complementary dialysis modality as stated elsewhere [12]. Besides, in spite of treatment with PD and HD in combination, approximately 45% of patients left from PD therapy.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previously, we reported that the mean age of patients who selected "PD first" were younger compared with that of patients on HD [16]. In the present study, there were no differences in mean age of patients who needed HD as complementary dialysis modality and those patients who started PD as "PD first", indicating that a larger portion of PD patients needed HD as complementary dialysis modality as stated elsewhere [12]. Besides, in spite of treatment with PD and HD in combination, approximately 45% of patients left from PD therapy.…”
Section: Discussionsupporting
confidence: 72%
“…Combination therapy with HD and PD allows for the partial separation of the two essential components of effective RRT, i.e., fluid removal and solute clearance [8][9][10][11][12][13]. In spite of using PD and HD in combination, peritoneal membranes gradually lose the ability to maintain adequate dialysis and many patients switch to HD only [14].…”
Section: Introductionmentioning
confidence: 99%
“…Additional use of PD also has inherent risks of the complications of both therapies, both in terms of access and cumulative metabolic stress. However, PD and HD have been used in a combined approach 30 in patients failing on either initial solo modality or even de novo at the start of renal replacement therapy. 31 Peritoneal dialysis versus hemodialysis.…”
Section: Specific Dialysis-related Risksmentioning
confidence: 99%
“…There are several types of PDþHD employed worldwide. 35 In Japan, PDþHD is mainly used for long-term PD patients to continue PD after loss of RRF. 25,26 Indeed, most PDþHD patients in this study had transferred from PD due to fluid overload and/or underdialysis after RRF decline.…”
Section: Discussionmentioning
confidence: 99%